Radiothermoluminescence of the γ-irradiated compositions of the ultra-high-molecular-weight polyethylene with nano-α-SiO₂ - Maharramov, A.M.; Ismayilova, R.S.; Quliyev, M.M.; Mamedova, R.L. (Вопросы атомной науки и техники, 2020)
Radiothermoluminescence (RTL) of the ultra-high-molecular-weight polyethylene (UHMWPE) and nanocomposites obtained on its base via introduction of nanofiller α-SiO₂ (aerosil) to its volume is studied. Two relaxation processes (α- and β-relaxations) are observed in these composites, whose maximums of thermoluminescence appear at temperatures 205 and 212 K, correspondingly. Features of the RTL spectra in dependence from the α-SiO₂ concentration at the absorbed radiation dose 1·10⁴ Gr are highlighted. Вивчено радіотермолюмінесценції (РТЛ) надвисокомолекулярного поліетилену (НВМПЕ) і нанокомпозитів, отриманих на його основі введенням в обсяг полімеру нанонаповнювача α-SiO₂ (аеросил). У цих композитах спостерігається два релаксаційних процеса (α-, β-релаксації) з максимумами термолюмінесценції при температурах 205 і 212 К відповідно. Виявлено особливості спектрів РТЛ у залежності від концентрації α-SiO₂ при поглиненій дозі опромінення в 1·10⁴ Гр. Изучены радиотермолюминесценции (РТЛ) сверхвысокомолекулярного полиэтилена (СВМПЭ) и нанокомпозиты, полученные на его основе введением в объем полимера нанонаполнителя α-SiO₂ (аэросил). В этих композитах наблюдаются два релаксационных процесса (α-, β-релаксации) с максимумами термолюминесценции при температурах 205 и 212 К соответственно. Выявлены особенности спектров РТЛ в зависимости от концентрации α-SiO₂ при поглощенной дозе облучения в 1·10⁴ Гр.